Tinjauan Perancangan Produksi dan Kualitas Pada Produk Rak Dies di CV Sarana Sejahtera Tehnik - Muhammad Syauqi Abdul Fath; Rizki Achmad Darajatun (Jurnal Ilmiah Wahana Pendidikan, 2022)
Industrial engineering as a science emerges and develops to meet the need for skilled experts in managing production systems or industrial systems, which involve human components, materials, and machines or production facilities. Industrial engineering discipline also concerns the management of production factors by prioritizing the right location and social. The purpose of this study was to determine the flow of the production process, to find out the problem points of the product, and to provide suggestions for the work process to minimize the product using the Basic Seven Tools method. The results obtained indicate that the level of quality control at CV Sarana Sejahtera Tehnik is still minimal. Control that can be done is in the form of a more in-depth analysis of the source of the problem, by using the analysis of seven basic tools, it will be seen the shortcomings that lead to the achievement of the Dies Rack product.